KEPUASAN PENGGUNAAN KACAMATA DAN SOFTLENS DI OPTIK TANJUNG PINANG TAHUN 2023 - Rika Ismawati; Febri Maryani; Murni Simarmata; Bunyamin Rizky Abdillah; Meisha Azhrany (Akademi Refraksi Optisi dan Optometry Gapopin, 2023)
Based on sales data at Optik Tanjung Pura, there has been a decline in sales of contact lenses compared to glasses. The decline occurred by around 10% from January 2023 to April 2023. In addition, during interviews with several customers, they were dissatisfied with contact lens products. The purpose of this study was to see the level of customer satisfaction with soft lenses and glasses and the factors that influence the level of satisfaction at Optic Tanjung Pinang. Qualitative research methods, conducting in-depth interviews with five customer informants of Optic Tanjung Pinang. The instrument used is a questionnaire, using the SERVQUAL method with five dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. The sampling technique uses a purposive sampling technique. The results obtained on the dimensions of tangibles, customers of glasses products are satisfied because the products are diverse, while contact lenses are still limited. On the reliability dimension of the officers in conveying information on both glasses and soft lens products, it is quite satisfying. The responsiveness dimension of the attitude of the optician has satisfied the customer. The conclusion is the level of customer satisfaction of glasses users based on the five dimensions of SERVQUAL, the results have satisfied customers, while contact lenses are considered unable to provide satisfaction to customers because they have a small number of contact lens collections, are incomplete, and are less varied.